XENODERMAL GRAFTS SATURATED WITH SILVER NANOPARTICLES IN PREPARATION FOR PLASTIC CLOSURE OF POSTOPERATIVE WOUNDS IN PATIENTS WITH NECROTIZING FASCIITIS - Stoianovskyi, Ihor; Khimich, Sergii; Tuzyuk, Natalya (Eastern Ukrainian Medical Journal, 2025)
Introduction. Necrotizing fasciitis (NF) is a severe infection associated with substantial tissue loss and a high risk of wound surface contamination. Standard xenodermal implants used for temporary coverage of postoperative defects frequently experience recurrent bacterial colonization.Objective was to evaluate the effectiveness of lyophilized xenodermal implants saturated with silver nanoparticles in improving the preparation of postoperative wounds for autografting in patients with NF.Materials and Methods. The study involved 20 patients with wounds following NF debridement. Patients were divided into two groups: the experimental group received lyophilized xenodermal implants saturated with silver nanoparticles, while the control group received standard xenodermal implants. Evaluations included granulation tissue formation speed suitable for autografting, incidence of secondary infections, and xenodermal implant adhesion duration.Results. The mean time for granulation tissue formation suitable for grafting in the experimental group was 9.2 ± 0.7 days compared to 14.5 ± 1.1 days in the control group (p<0.05). No secondary infections occurred in the experimental group, whereas the control group had 3 cases. The adhesion duration of xenodermal implants was significantly longer in the experimental group (4.5±0.4 days versus 2.8±0.25 days, p<0.05).Conclusions. Using xenodermal implants saturated with silver nanoparticles facilitates faster granulation tissue formation, reduces bacterial complication risk, and enhances preparation outcomes for postoperative wound closure.